KALÃM AL-INSHÃ AT-THALABI FI KITÃB AL-AKHLÃQ LIL BANIN AL-JUZ’U AL-THÃNI - Setiawan, Hendra (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
In the Second Part of Kita>b Al-Akhla>q Lil Bani>n  by Shaykh Omar Baraja who died in 1411 Hijriya, found ways of commanding, prohibition, asking, wishful thinking and calling. The purpose of this study is to find out the methods of speech of order creation that the author uses in his advice and be able to break them down according to their types. This type of research is desk study, which means that it collects data from various books related to the subject of scientific research. The result of his research is that in this book there are 169 speeches of order creation which include commands, prohibitions, interrogatives, and exclamations. And the researcher didn’t wishful thinking in this book. There are one hundred and four sentences of command methods in three forms, those are fi’il al-amr, al-muda>ri’ al-majzu>m bi la>m al-amr and ismu fi’il al-amr. There are twenty three sentences of prohibition methods in one form, that is present tense with la> al-na>hiyah. There are twenty three of interrogative methods that use one of these tools, namely hamzah, ayyu, ma>, hal, kam, and man. There are nineteen sentences of calling methods using one of these tools, namely hamzah, ayyu, and ya>. And Researcher didn’t find wishful thinking style in this book.اكتشف في كتاب الأخلاق للبنين الجزء الثاني للشيخ عمر بارجاء المتوفى سنة  1411 ه  أساليب الأمر والنهي والاستفهام والتمني والنداء. فغرض هذا البحث هو معرفة أساليب كلام الإنشاء الطلبي التي استعملها المؤلف في نصيحته وقدرة على تفصيلها على حسب جنسها. أما نوع هذا البحث بحث مكتبي أي جمع البيانات من الكتب المتنوعة التى تتعلّق بموضوع البحث العلمي. نتيجة البحث أن في هذا الكتاب 169 أسلوب من كلام الإنشاء الطلبي التي تتضمن الأمر و النهي و الاستفهام والنداء. وما وجد الباحث أسلوب التمني في هذا الكتاب. أما أساليب الأمر مائة وأربع جملة على ثلاث صيغات هي فعل الأمر والمضارع المجزوم بلام الأمر واسم فعل الأمر. وأساليب النهي ثلاث وعشرون جملة على صيغة واحدة هي المضارع مع لا الناهية. وأساليب الاستفهام ثلاث وعشرون جملة بأداة من هذه الأدوات وهي الهمزة و أَيُّ و مَا و هَلْ و كَمْ و مَنْ. وأساليب النداء تسع عشرة جملة بأداة من هذه الأدوات وهي الهمزة و أَيُّ و يَا. وما وجد الباحث أسلوب التمني في هذا الكتاب.